Implementing The Total Quality Management (TQM) Model in Healthcare Institutions - Aruna , Dr.V.; Damodaraswamy , Dr. Anandhi; Rajapriya , Dr.M.; Sharma, Dr. Ravinder (International Journal of Accounting and Economics Studies, 2025)
Total Quality Management (TQM) is a systematic approach aimed at enhancing healthcare service quality by fostering a culture of continuous improvement, patient-centered care, and operational efficiency. The authors examine the application of the TQM model in health care organizations and how it affects the delivery of services, as well as patients' satisfaction and hospital performance. The critical components of TQM, including the demand for leadership commitment, employee participation, process efficiency, and decisions based on statistical analysis, are reviewed. Concerns in TQM implementation emphasized in the study included a lack of resources, resistance to change, and the need for training programs. What the studies demonstrate is that when Total Quality Management becomes successfully interspersed with healthcare, patients benefit, costs decrease, and healthcare efficiency increases. The study concludes with a few more critical directions for health care organizations to take. It should incorporate best practices of Total Quality Management, so it becomes better and better at managing quality from year to year.